Testing and update of mind mapping software that helps students to plan eight different types of essays - Chowdhury, Ishfaqul Hoque (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2007.